Adverbs of Manner Found in “Harry Potter”: Forms and Positions: - Juliarta, I Made; Wirawan, I Gede Nika (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This study analyses the forms and positions of adverbs of manner found in the novel Harry Potter. It aims to identify how adverbs of manner function within clause and sentence structures. The analysis is based on the theory proposed by Brown and Miller (1991), supported by other relevant linguistic theories. A qualitative method was applied through library research, with data taken directly from the novel. The findings reveal two primary forms of adverbs of manner: those formed by adding the suffix –ly to adjectives and those structured as prepositional phrases. These adverbs typically occupy various positions within sentences, often characterized by their syntactic flexibility. The study concludes that adverbs of manner in Harry Potter are predominantly formed through morphological and phrasal processes, serving diverse syntactic roles. The findings reveal two primary forms of adverbs of manner: those formed by adding the suffix –ly to adjectives and those structured as prepositional phrases. These adverbs typically occupy various positions within sentences, often characterized by their syntactic flexibility. The study concludes that adverbs of manner in Harry Potter are predominantly formed through morphological and phrasal processes, serving diverse syntactic roles.